Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ypmed.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Personal and provider level factors influence participation to cervical cancer screening: A retrospective register-based study of 1.3 million women in Norway

Abstract: High coverage is essential for an effective screening programme. Here we present screening barriers and facilitators among 1.3 million women aged 25-69years eligible for screening within the Norwegian Cervical Cancer Screening Program (NCCSP). We defined non-adherence as no screening test in 2008-2012. We divided adherent women into those screened spontaneously, and those who had a smear after receiving a reminder from the NCCSP. Explanatory variables were extracted from several nationwide registers, and model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…The women are advised to make appointment with their general practitioner for cervical cancer screening. A retrospective register-based study of 1.3 million women in Norway showed that 50% of immigrant women were non-adherent compared to 31% of native Norwegians [8]. Nonetheless, statistics about the burden of cervical cancer among immigrant women in Norway are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The women are advised to make appointment with their general practitioner for cervical cancer screening. A retrospective register-based study of 1.3 million women in Norway showed that 50% of immigrant women were non-adherent compared to 31% of native Norwegians [8]. Nonetheless, statistics about the burden of cervical cancer among immigrant women in Norway are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The results of several studies suggest that socioeconomic differences play an important role in the incidence, mortality and survival rate of cervical cancer (Akinyemiju et al, 2016;Ibfelt et al, 2013;Kim and Kang, 2016;Ueda et al, 2006). This is associated with a variety of factors, such as low access to screening (Leinonen et al, 2017), non-implementation of prevention programs (Chidyaonga-Maseko et al, 2015), ineffective and inadequate treatment, and poor sanitary conditions (Benard et al, 2008;Ganesan et al, 2015;Rossi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer. 8,9 The low screening attendance and advanced breast cancer stage distribution reported for non-Western immigrants may contribute to poor cancer survival. 8,9 The low screening attendance and advanced breast cancer stage distribution reported for non-Western immigrants may contribute to poor cancer survival.…”
mentioning
confidence: 99%
“…7 Non-Western immigrants have also been shown to have lower attendance rate to both cervical and mammography screening. 8,9 The low screening attendance and advanced breast cancer stage distribution reported for non-Western immigrants may contribute to poor cancer survival.…”
mentioning
confidence: 99%